A comparison of working in small-scale and large-scale nursing homes: A systematic review of quantitative and qualitative evidence. (February 2017) - Vermeerbergen, Lander; Van Hootegem, Geert; Benders, Jos
Abstract: Background and objective: Ongoing shortages of care workers, together with an ageing population, make it of utmost importance to increase the quality of working life in nursing homes. Since the 1970s, normalised and small-scale nursing homes have been increasingly introduced to provide care in a family and homelike environment, potentially providing a richer work life for care workers as well as improved living conditions for residents. 'Normalised' refers to the opportunities given to residents to live in a manner as close as possible to the everyday life of persons not needing care. The study purpose is to provide a synthesis and overview of empirical research comparing the quality of working life – together with related work and health outcomes – of professional care workers in normalised small-scale nursing homes as compared to conventional large-scale ones. Design: A systematic review of qualitative and quantitative studies. Data sources: A systematic literature search (April 2015) was performed using the electronic databases Pubmed, Embase, PsycInfo, CINAHL and Web of Science. References and citations were tracked to identify additional, relevant studies. Review methods: We identified 825 studies in the selected databases. After checking the inclusion and exclusion criteria, nine studies were selected for review. Two additional studies were selected after reference and citation tracking. Three studies were excluded after requesting more information on the research setting. Results: The findings from the individual studies suggest that levels of job control and job demands (all but "time pressure") are higher in normalised small-scale homes than in conventional large-scale nursing homes. Additionally, some studies suggested that social support and work motivation are higher, while risks of burnout and mental strain are lower, in normalised small-scale nursing homes. Other studies found no differences or even opposing findings. The studies reviewed showed that these inconclusive findings can be attributed to care workers in some normalised small-scale homes experiencing isolation and too high job demands in their work roles. Conclusion: This systematic review suggests that normalised small-scale homes are a good starting point for creating a higher quality of working life in the nursing home sector. Higher job control enables care workers to manage higher job demands in normalised small-scale homes. However, some jobs would benefit from interventions to address care workers' perceptions of too low social support and of too high job demands. More research is needed to examine strategies to enhance these working life issues in normalised small-scale settings.